2012
DOI: 10.1038/cdd.2012.129
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Atg5 by the Gadd45β–MEKK4-p38 pathway inhibits autophagy

Abstract: Autophagy is a lysosomal degradation pathway important for cellular homeostasis, mammalian development, cancer and immunity. Many molecular components of autophagy have been identified, but little is known about regulatory mechanisms controlling their effector functions. Here, we show that, in contrast to other p38 MAP kinase activators, the growth arrest and DNA damage 45 beta (Gadd45b)-MAPK/ERK kinase kinase 4 (MEKK4) pathway specifically directs p38 to autophagosomes. This process results in an accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 40 publications
4
91
0
2
Order By: Relevance
“…Previous work has shown that ERK1/2 inhibits phosphorylation of p38 (35), which is a negative regulator of autophagy (23,36). We found that p38 phosphorylation was increased in the livers of db/db mice, and the increased p38 phosphorylation was significantly decreased by Ad-CA MEK1 in the livers of db/db mice or primary hepatocytes ( Fig.…”
Section: Erk1/2 Regulates Atg7 and Autophagy In A P38-dependent Pathwsupporting
confidence: 55%
“…Previous work has shown that ERK1/2 inhibits phosphorylation of p38 (35), which is a negative regulator of autophagy (23,36). We found that p38 phosphorylation was increased in the livers of db/db mice, and the increased p38 phosphorylation was significantly decreased by Ad-CA MEK1 in the livers of db/db mice or primary hepatocytes ( Fig.…”
Section: Erk1/2 Regulates Atg7 and Autophagy In A P38-dependent Pathwsupporting
confidence: 55%
“…For example, MAPK8/JNK1 plays a critical role in the early steps of autophagy whereas the MEKK4-MAPK/p38 axis-induced phosphorylation of ATG5 blocks autophagic flux in a late stage. 5,37 Recently, SUPT20H/p38IP was shown to bind to ATG9 and to be essential for starvation-induced autophagy. 38 We think that identification of the remaining phosphorylation site(s) and the relevant kinase(s) should provide useful information for a better understanding of the cellular function of ATG16L1.…”
Section: Discussionmentioning
confidence: 99%
“…During expansion, the cytoplasmic contents are directly enclosed by the double-membrane phagophore, and a complete autophagosome is generated; the autophagosome then fuses with a lysosome to degrade its cargo. 5 Autophagosome maturation requires a series of ubiquitin-like conjugation events that mainly involves the LC3-phosphatidylethanolamine (PE) and the ATG12-ATG5-ATG16L1 conjugation systems. These core ATG proteins, including ATG16L1, are indispensable in the generation of the autophagosome.…”
mentioning
confidence: 99%
“…We monitor the S. aureusdependent induction of autophagosome formation by using NIH/3T3 fibroblasts stably expressing the autophagosomal marker GFP-MAP1LC3B, hereafter short GFP-LC3B. 11,21 Cells were infected with the RFP-expressing S. aureus strain SH1000-RFP and subsequently analyzed via imaging over a defined time period. The appearance of an increasing number of GFP-LC3B-positive puncta in the cytosol of the host cells can be an indication of enhanced autophagosomal formation.…”
Section: Induction Of the Autophagic Response During S Aureus Infectionmentioning
confidence: 99%